DEPTOR Prevents Osteoarthritis Development Via Interplay With TRC8 to Reduce Endoplasmic Reticulum Stress in Chondrocytes. (24th September 2020) - Li, Kai; Yang, Panpan; Zhang, Yuwei; Zhang, Yue; Cao, He; Liu, Peilin; Huang, Bin; Xu, Song; Lai, Pinglin; Lei, Guanghua; Liu, Jia; Tang, Yujin; et al.
ABSTRACT: Endoplasmic reticulum (ER) stress has been shown to promote chondrocyte apoptosis and osteoarthritis (OA) progression, but the precise mechanisms via which ER stress is modulated in OA remain unclear. Here we report that DEP domain‐containing mTOR‐interacting protein (DEPTOR) negatively regulated ER stress and OA development independent of mTOR signaling. DEPTOR is ubiquitinated in articular chondrocytes and its expression is markedly reduced along with OA progression. Deletion of DEPTOR in chondrocytes significantly promoted destabilized medial meniscus (DMM) surgery‐induced OA development, whereas intra‐articular injection of lentivirus‐expressing DEPTOR delayed OA progression in mice. Proteomics analysis revealed that DEPTOR interplayed with TRC8, which promoted TRC8 auto‐ubiquitination and degraded by the ubiquitin–proteasome system (UPS) in chondrocytes. Loss of DEPTOR led to TRC8 accumulation and excessive ER stress, with subsequent chondrocyte apoptosis and OA progression. Importantly, an inhibitor of ER stress eliminated chondrocyte DEPTOR deletion‐exacerbated OA in mice. Together, these findings establish a novel mechanism essential for OA pathogenesis, where decreasing DEPTOR in chondrocytes during OA progression relieves the auto‐ubiquitination of TRC8, resulting in TRC8 accumulation, excessive ER stress, and OA progression. Targeting this pathway has promising therapeutic potential for OA treatment. © 2020 American Society for Bone and Mineral Research (ASBMR).